1960-1980 arası dönemde İstanbul imalat sanayi - Keleşoğlu, Sena (My University, 2012)
stanbul, İstanbul Sanayi, Planlama, Sanayi İşkolları ÖZET Sanayi devrimi ile birlikte dünyada sanayileşme olgusu hızlı bir şekilde gerçekleşmiş, ancak Osmanlı Devleti bu hızlı değişime ayak uyduramamıştır. Geleneksel korumacı ekonomik politikaların uygulanmasını kolay terk edemeyen Osmanlı ekonomisi, sanayi devrimi öncesindeki popülaritesini daha sonraki dönemlerde yeniden edinememiştir. Cumhuriyetin ilk yıllarında edinilen yeni üretim anlayışına göre, gelişmenin sanayileşme olgusuyla birlikte gerçekleştirileceği fikri benimsenmiş, sanayileşme devlet eliyle gerçekleştirilmeye çalışılmıştır. 1960’lı yılların Kalkınma Planları, sınai gelişme doğrultusunda atılan en ciddi adım olmuş, Türkiye ekonomisinde 1960-1980 arası Kalkınma Planları döneminde ithal ikameci politikalar uygulamaya alınmıştır. Bu çalışmada 1960-1980 arası dönemde İstanbul imalat sanayi ele alınmıştır. 1960’lı yıllarda hız kazanan sanayileşme olgusunun İstanbul ilindeki yansımaları, gerçekleşme dereceleri ve sanayileşme faaliyetlerinde etkili olan faktörler gösterilmiş, işkolları ayrı ayrı incelenmiştir. İstanbul sanayi, kentin merkez bölgelerinde gerçekleştirdiği gelişimini kentsel zorunluluklar sebebiyle şehrin dış kesimlerine doğru ve büyüyerek devam ettirmiştir. İstanbul’un nüfusunun gittikçe daha yoğun bir hale gelmesi ve Türkiye topraklarında sanayi için uygun alanların mevcut bulunması sebepleriyle, İstanbul dışına sanayi göçleri başlamıştır. Istanbul, Istanbul Industry, Planning, Industrial Sectors

A case with the industrial revolution, rapid industrialization took place in the world, but it did not keep pace with this rapid change of the Ottoman Empire. The implementation of protectionist economic policies that can not easily abandon the traditional Ottoman economy before the industrial revolution was unable to regain its popularity in later times. According to a new conception to production from the early years of the republic, adopted the idea of development will take place together with the fact of industrialization, industrialization is being carried by the state. Development Plans of the 1960s, the most serious step was taken in line with industrial development, Turkey's economy between 1960-1980 Development Plans have been implemented during the import substitution policies. Manufacturing industry in Istanbul during the period between 1960-1980 in this study are discussed. Reflections in the province of Istanbul in the 1960s phenomenon of accelerated industrialization, and industrialization activities, factors that influence the realization shown in degrees, sectors are examined separately. Istanbul industry, the city's central areas of the outer parts of the city due to requirements and performs urban development has continued to grow. Istanbul and Turkey's population becomes more and more intense to be present territory of the areas suitable for industrial reasons, the industry began to emigrate out of Istanbul.
Keywords: Ekonomi Planlaması; Sanayi; Şehir Planlaması_İstanbul (Türkiye)